The Effect of the "Evoking Freedom" Technique on an Unusual and Disturbing Request. Issue 3 (June 2015) - Guéguen, Nicolas; Silone, Fabien; David, Mathieu; Pascual, Alexandre
The "evoking freedom" technique consists in soliciting someone to comply with a request by simply saying that she is free to accept or to refuse the request. However, previous studies used low cost requests. The present study examined the magnitude of this technique associated with a more disturbing and costly request. Sixty men and 60 women aged approximately 20–25 years walking in the street were asked by a male confederate to hold a closed transparent box containing a live trap-door spider while he went into the post office to pick up a package. In the evoking freedom condition, the confederate added in his request that the participant was "free to accept or to refuse." More compliance occurred in the "evoking freedom" condition (53.3%) than in the control condition (36.7%). These results confirm the robustness and the magnitude of the evoking freedom technique on compliance and show that this technique remained effective even when the request was psychologically costly to perform and was associated with fear.